New agents to treat lower urinary tract and pelvic floor disorders - Kelleher, Cornelius (Canadian Urological Association Journal, 2013)
For patients with overactive bladder and a suboptimal response to antimuscarinic therapy, there are several options to consider including alteration of the antimuscarinic regimen, switching to an agent with an alternate mechanism of action (i.e., mirabegron), posterior tibial nerve stimulation, or botulinum toxin. These options are summarized in this brief review.